Isentropic diagnostics of mean circulation and water vapour budget for the Asian monsoon - Lee, Shao Yi (2012)
The observed Hadley spends most of the year in an asymmetrical state with the win- ter cell dominant. The asymmetrical Hadley reflects the seasonal evolution of the monsoon circulation, since only the monsoon trough seasonally migrates through a large span of latitudes while the location of the oceanic ITCZ remains comparatively fixed. The observed Hadley is often used for comparisons with model-produced global mean meridional circulations. These comparisons may not reflect the actual dynamical regimes that local “Hadleys” lie in, because the global zonal mean meridional circulation is not representative of the meridional circulation in the monsoon and oceanic regions. Therefore, a sectoral zonal mean (“sec-mean”) covering only the Asian monsoon region was applied to pentad-average Japanese 25-year Reanalysis.